Pendampingan Pembelajaran Praktik Sholat Dengan Menggunakan Media Audio Visual - Nulinnaja, Ratna; Misbahul Munir; Kivah Aha Putra (PT. ALHAFI BERKAH INDONESIA, 2024)
This service assistance is a classroom observation study conducted in Petungsewu Village, especially in the educational context. The focus of the research is the use of audio-visual learning facilities, where material is delivered via video. The equipment used involves a projector and sound system provided by the school, aimed at ensuring that learning can take place optimally and conducively. The research results show that students show higher interest in audio-visual media in this lesson. This is because audio-visual media is in line with the tendencies of today's children who like to play games on gadgets. Students have a tendency to like learning that is not monotonous and is equipped with interesting games. The existence of children's films also has a positive influence on this learning, because it suits their dominant interests. With practice and interesting game interludes, students also understand the learning material more easily.